PERBANDINGAN PENYELESAIAN SENGKETA MEREK BERDASARKAN UNDANG-UNDANG MEREK NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS JO. UNDANG-UNDANG NOMOR 30 TAHUN 1999 TENTANG ARBITRASE DAN ALTERNATIF PENYELESAIAN SENGKETA DENGAN WORLD INTELLECTUAL PROPER - Shelly Kurniawan (Faculty of Law, Maranatha Christian University, 2019)
Dispute resolution does not only have to go through court, it can also resolve by alternative dispute resolution. Alternative dispute resolution regulated in Indonesia through Act Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution that more diverse than alternative dispute resolution provided by the World Intellectual Property Organization (WIPO) through the WIPO Arbitration and Mediation Centre. Alternative dispute resolution in Indonesia can be in consultation, mediation, negotiation, conciliation, arbitration, and expert determination. The WIPO Arbitration and Mediation Centre at least provides four option for the alternative dispute resolution, namely mediation, arbitration, expedited arbitration, and expert determination. This research is to compare the alternative dispute resolution in marks dispute resolution jo. the act of alternative dispute resolution and alternative dispute resolution on WIPO Arbitration and Mediation Centre. Only expedited arbitration that is not explicitly regulated in Act Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, but there is provisions that resemble to expedited arbitration, i.e. a sole arbiter